Comprehensive Review of the Literature on Human Capital in the Context of Economic Development - Wako Jio; Chalchissa Amentie KERO (RADINKA JOURNAL OF SCIENCE AND SYSTEMATIC LITERATURE REVIEW, 2023)
This work aims to explore the relationship between human capital and economic growth. The study looks at previous research on the connection between economic growth and human capital, analyses datasets from other studies, and draws some conclusions. The paper summarises articles on human capital with respect to (i) the new endogenous theory, (ii) the neo-classical growth model, (iii) the the economist growth production-function, (iv) the conceptual framework of economic growth theory, and (v) empirical evidence on the relationship and causal connection between human capital and economic growth. Assessing the corpus of research on human capital and economic growth will yield an extensive literature guide for creating short- and long-term developmental goals for any region, as well as for creating and carrying out policies.